Detection of Micronucleus, Nucleoplasmic Bridges, and Nuclear Buds Frequency in Peripheral Blood Lymphocytes of Cancer Patient Post-Radiation Fractionated - Teja Kisnanto; Yanti Lusiyanti; Dyah Erawati; Suryadi (Nusantara Science and Technology Proceedings)
Simple measurement of cytogenetic damage would be of great value for studying genetic risk factors, especially in radiotherapy for cancer patients. One cytogenetic technique that is easy and simple to quantify the damage caused by radiation exposure in cultured human lymphocytes is the micronucleus (MN). This research was conducted to study the induction of micronucleus (MN), Nucleoplasmic Bridge (NPB), and Nuclear Buds (NBUDs) in cancer patients after administration of fractionated radiation exposure total of 20 Gy. Peripheral blood lymphocyte samples obtained from eleven cancer patients as the study group and eleven from the healthy people as the control group were assessed. Both samples were then cultured and added cytochalasin-B to arrest cells during the cytokinesis stage. Its characteristics were observed in binucleated cells (BNC) with cytochalasin blocked micronuclei (CBMN) assay procedure. The number of MN, NPB, and NBUDs was evaluated per 1000 BNC for both the study group and control. The results showed that there was a statistically signif- icant difference (P <0.05) between the frequency of MN in the study group (82.18±39.93) compared to controls (13.18±4.94). Besides, the number of NPB and NBUD in the study group is relatively low. In conclusion, the iden- tification of MN formation in peripheral blood lymphocytes of post-radiation cancer patients has other molecular mechanisms such as NPB and NBUD. Also, demographic factors such as age can influence the appearance of MN, NPB, and NBUDs.